ZAR1 and ZAR2 orchestrate the dynamics of maternal mRNA polyadenylation during mouse oocyte development - Yu-Ke Wu; Ruibao Su; Zhi-Yan Jiang; Yun-Wen Wu; Yan Rong; Shu-Yan Ji; Jingwen Liu; Zhuoyue Niu; Zhiyi Li; Yuanchao Xue; Falong Lu; Heng-Yu Fan (Genome Biology)
Abstract Background During meiosis, the oocyte genome keeps dormant for a long time until zygotic genome activation. The dynamics and homeostasis of the maternal transcriptome are essential for maternal-to-zygotic transition. Zygotic arrest 1 (ZAR1) and its homolog, ZAR2, are RNA-binding proteins that are important for the regulation of maternal mRNA stability. Results Smart-seq2 analysis reveals drastically downregulated maternal transcripts. However, the detection of transcript levels by Smart-seq2 may be biased by the polyadenylated tail length of the mRNAs. Similarly, differential expression of maternal transcripts in oocytes with or without Zar1/2 differs when analyzed using total RNA-seq and Smart-seq2, suggesting an influence of polyadenylation. Combined analyses using total RNA-seq, LACE-seq, PAIso-seq2, and immunoprecipitation-mass spectrometry reveals that ZAR1 may target the 3’-untranslated regions of maternal transcripts, regulates their stability in germinal vesicle stage oocytes, and interacts with other proteins to control the polyadenylation of mRNAs. Conclusions The jointly analyzed multi-omics data highlight the limitations of Smart-seq2 in oocytes, clarify the dynamics of the maternal transcriptome, and uncover new roles of ZAR1 in regulating the maternal transcriptome.